Applying machine learning to marketing : implementation and management of a next best offer recommendation model in the financial industry - Valtonen, Anna (2020)
This Master’s Thesis researches how a predictive analytics next best offer (NBO) recommendation model is developed, implemented and managed in a Finnish retail bank. This Thesis studies how the NBO model is strategically employed as a customer-oriented marketing communications tool in marketing, customer service and customer relationship management (CRM). The NBO model predicts the customers’ interest in the products and services the case bank offers and prioritizes the recommendations. Then, the recommendations are used to target marketing communications messages based on customers’ interest. With the help of the NBO model, the case bank has reached better conversion rates, optimized marketing budget, increased customer experience and increased sales. The goal of this research is to study the successes and challenges in the implementation and management of the NBO model in the case bank located in Finland. Further, this Thesis studies the best practices and challenges in evaluating the NBO model performance. The research goal is achieved by thoroughly studying what kind of challenges and facilitators can emerge in the implementation and management of an NBO model. The key findings and the perceived benefits of an NBO model are presented. The main theoretical background centers upon NBO as a customer-centric marketing tool, adoption, implementation and management of predictive analytics, and data-driven decision-making. The research findings are analyzed based on the themes derived from the theoretical background and research findings, including implementation, management and NBO performance evaluation. This research complements the existing research literature on predictive analytics implementation and management. This research found several consistencies with prior literature, including the importance of involving employees to the implementation, importance of clear communication and adequate training, and the significance of centralized cross-functional management. Further, this research completes the earlier research for example with the importance of documentation and significance of careful planning and continuous testing in the implementation and management of a NBO model.